RAGAM BAHASA DALAM REEL INSTAGRAM AROFTATV: KESALAHAN YANG SERING TERJADI SAAT TAKBIR INTIQAL (ANALISIS DESKRIPTIF) - Moh. Dzaky Amrullah; Dwi Rizaldi Mualimin; Nurfatma Khumairo Yusufiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and analyze the language varieties used in an Aroftatv Instagram reel, which discusses common mistakes during takbir intiqal delivered by Sheikh Amir bin Muhammad Fida Bahjat. The research employs a descriptive analysis method, with data collection involving the transcription of spoken language from the video into written text. A total of 138 words were classified into 23 sentences and analyzed contextually based on the theories of standard language, dialects, and registers. The findings reveal that the language used in the reel is a combination of standard Arabic and regional dialects. Specifically, 12 sentences use standard language, while 11 sentences contain dialects, primarily Saudi Arabian and Egyptian regional dialects. The dialectal differences encompass variations in letter pronunciation, letter substitution, and specific word or phrase choices. Due to the mixture of standard language and dialects, the dominant language variety is classified under the consultative register and religious register. This classification perfectly aligns with the context of the speech, which focuses on Islamic prayer procedures delivered verbally in a teacher-student dynamic.